2010
DOI: 10.1634/theoncologist.2010-0090
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Chronic Lymphocytic Leukemia—The Price of Progress

Abstract: The study looks at the high cost of new treatments for chronic lymphocytic leukemia and calls for the consideration of a standardized and transparent method to determine the price of new drugs based on comparative effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…In this regard, the physician charge for a second opinion by a disease expert is a relatively low cost intervention($$600), roughly 1% of the average wholesale price of 6 cycles of first-line CLL therapy. 43 When a disease-specific expert is not available, patients should be managed according to published treatment guidelines developed by expert panels.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the physician charge for a second opinion by a disease expert is a relatively low cost intervention($$600), roughly 1% of the average wholesale price of 6 cycles of first-line CLL therapy. 43 When a disease-specific expert is not available, patients should be managed according to published treatment guidelines developed by expert panels.…”
Section: Discussionmentioning
confidence: 99%
“…GNP alone has shown some response with induction of apoptosis in some of these CLL cells. Phase II clinical studies conducted on 46 CLL patients concluded that while anti-VEGF therapy, including avastin, remains a viable therapy for CLL, using a single agent anti-VEGF monotherapy had limited activity in CLL patients, and combination therapy is a more feasible approach particularly for patients with relapsed/refractory CLL ( 61 ). The combination of monoclonal antibodies, such as anti-CD20 or rituximab, with other types of chemotherapy is another promising approach for treatment in CLL ( 62 ).…”
Section: Nanotechnology Applications In Different Types Of Leukemimentioning
confidence: 99%
“…Because most patients with CLL are not diagnosed or treated until they are over the age of 65 years,1 the cost of these therapies in the US are likely to be paid for by Medicare 10. In the Medicare patient population, diagnosis of CLL between 1998 and 2002 was associated with significantly increased costs of approximately $33,000 per year versus Medicare patients without a cancer diagnosis 11.…”
Section: Introductionmentioning
confidence: 99%